How to be the Best You Can - Anka, Carl (UK, 2021)
It's hard to know what's possible until you start. You have to be able to dream big and be prepared to work towards your dreams. I've achieved a lot so far, but it didn't come in one go; Big things rarely happen overnight, and good things rarely happen as if by magic... This book is full of stories from Marcus's own life, brilliant advice and top-tips from performance psychologist...
Keywords: Biography; Juvenile Non-Fiction; Marcus Rashford